Scratch + CNC: Mixing Physical and Digital Worlds - Maraschin Jr, Dirceu; Gutierres, Anderson; Primo, Tiago Thompsen (Anais do Workshop on Advanced Virtual Environments and Education (WAVE); 2020: Anais do III Workshop on Advanced Virtual Environments and Education, 2021)
Knowledge retention occurs most effectively when there is experimentation and there is an association between understanding what was learned conceptually and a real experience. We propose the development of an extension for Scratch 3.0 allowing the interaction with a CNC (Computer Numeric Control) machine. A proposal of cooperation between two environments in the learning context is created, combining programming in blocks with equipment able to provide outputs in physical objects.